2002
DOI: 10.1590/s0100-879x2002000600015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the acupoints ST-36 (Zusanli) and SP-6 (Sanyinjiao) on intestinal myoelectric activity of Wistar rats

Abstract: Despite its ancient use as a therapeutic tool to treat several ailments, acupuncture still faces the challenge of scrutiny by Western science both in terms of its efficacy and in terms of the characterization of its effects and mechanisms of actions underlying these effects. We investigated under well-controlled and carefully characterized conditions the influence of electrical stimulation of acupuncture points ST-36 (Zusanli) and SP-6 (Sanyinjiao) on the myoelectric activity of the small intestine of 38 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Electroacupuncture can be more effective than manual acupuncture to produce acupuncture effects [27] although there are little reports about comparison of them on gastrointestinal functions. Additionally, acupuncture at ST36 has been reported to increase intestinal motility [3,26]. Thus, the increase in intestinal motility reported by Luna et al [16] is presumed to be due to electroacupuncture or ST36 acupoint.…”
Section: ]mentioning
confidence: 99%
“…Electroacupuncture can be more effective than manual acupuncture to produce acupuncture effects [27] although there are little reports about comparison of them on gastrointestinal functions. Additionally, acupuncture at ST36 has been reported to increase intestinal motility [3,26]. Thus, the increase in intestinal motility reported by Luna et al [16] is presumed to be due to electroacupuncture or ST36 acupoint.…”
Section: ]mentioning
confidence: 99%
“…We have previously shown that acupuncture is effective in increasing and regulating the myoelectric activity of the small intestine (28). This effect was more intense in the proximal muscles of the duodenum.…”
Section: Discussionmentioning
confidence: 88%
“…1 Acupuncture has been used for the treatment of several diseases such as neurological 2 , musculoskeletal 3 , dermatological 4 , reproductive 5 , respiratory 6 and gastrointestinal problems 7,8 , otitis 9 and others. Acupuncture is a therapeutic method that uses physical and chemical stimulus on certain areas of the skin (acupoints) to stimulate body homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…8 age, disease, number of acupuncture sessions, kind of treatment (acupuncture, eletroacupuncture, homeopathy, moxibustion, gold implant, and their associations) and recovery rate. It was considered for the recovery rate only animals that had at least 50% of improvement on clinical signs according to the owners evaluation and clinical evaluation of at least two veterinarians.…”
mentioning
confidence: 99%